2015
DOI: 10.1093/gbe/evv057
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Divergence between Parental Alleles Determines Gene Expression Patterns in Hybrids

Abstract: Both hybridization and allopolyploidization generate novel phenotypes by conciliating divergent genomes and regulatory networks in the same cellular context. To understand the rewiring of gene expression in hybrids, the total expression of 21,025 genes and the allele-specific expression of over 11,000 genes were quantified in interspecific hybrids and their parental species, Coffea canephora and Coffea eugenioides using RNA-seq technology. Between parental species, cis- and trans-regulatory divergences affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
99
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 48 publications
(86 reference statements)
17
99
3
Order By: Relevance
“…The preponderant trans ‐effects on orthologous expression differences between the parental subspecies is consistent with the scenario that the attenuated allelic expression difference in the F1 hybrids is due to strong common trans ‐regulation (Figures and ). Our results pointing to more prominent trans ‐ than cis ‐effects are contrasted with several previous studies of interspecific differences in gene expression, which found higher cis ‐ than trans ‐ (Shi et al., ) or similar cis ‐ and trans ‐regulatory divergence (Bell, Kane, Rieseberg, & Adams, ; Combes et al., ). Together, it suggests that the relative importance of cis ‐ versus trans ‐regulatory divergence in the evolution of gene expression differences between inter‐ and intraspecies can be significantly different.…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…The preponderant trans ‐effects on orthologous expression differences between the parental subspecies is consistent with the scenario that the attenuated allelic expression difference in the F1 hybrids is due to strong common trans ‐regulation (Figures and ). Our results pointing to more prominent trans ‐ than cis ‐effects are contrasted with several previous studies of interspecific differences in gene expression, which found higher cis ‐ than trans ‐ (Shi et al., ) or similar cis ‐ and trans ‐regulatory divergence (Bell, Kane, Rieseberg, & Adams, ; Combes et al., ). Together, it suggests that the relative importance of cis ‐ versus trans ‐regulatory divergence in the evolution of gene expression differences between inter‐ and intraspecies can be significantly different.…”
Section: Resultscontrasting
confidence: 90%
“…However, we note that our RNA‐seq‐based genomewide assay of the same F1 hybrids and tetraploid rice plants of earlier generations (immediately following WGD, hence nonsegregating) produced virtually the same results (Xu et al., ). Moreover, several recent studies in diverse organismal systems also revealed significant attenuation of inherit parental expression divergence in interspecific F1 hybrids and/or allopolyploids (Bell et al., ; Combes et al., ; Cox et al., ; Shi et al., ). Therefore, it seems unlikely that our observation is due to biased selection of genes or their small number.…”
Section: Discussionmentioning
confidence: 99%
“…For faster-X expression divergence, this would require that differences in transcript abundances are due to divergence in cis-regulatory elements and/or X-linked trans-regulatory elements (Kayserili et al 2012;Meisel et al 2012a;Meisel and Connallon 2013). Several studies suggest that divergence in transcript abundances is largely determined by evolution in cis (Wittkopp et al 2004;Landry et al 2005;Wittkopp et al 2008;Graze et al 2009;Goncalves et al 2012;Shi et al 2012;Shen et al 2014;Mack et al 2016), while other research indicates that trans-regulatory divergence is more common (Emerson et al 2010;McManus et al 2010;Schaefke et al 2013;Coolon et al 2014;Meiklejohn et al 2014;Combes et al 2015) or that the inferred mode of regulatory divergence is dependent on taxon and experimental design (Coolon and Wittkopp 2013;Guerrero et al 2016). The mechanisms underlying the evolution of DNA methylation are even more poorly understood, but levels of DNA methylation within a given genomic region appear strongly Faster-X sequence evolution also assumes that beneficial mutations are on average at least partially recessive (Charlesworth et al 1987), while theory (Gibson and Weir 2005) and several empirical studies (Lemos et al 2008;McManus et al 2010;Schaefke et al 2013) suggest that cis-regulatory elements should on average act additively.…”
Section: Regulatory Evolution and Spermatogenesismentioning
confidence: 99%
“…These compensatory stabilizing regulatory processes may, however, give rise to immediate expression novelty following genomic merger, where different cis and trans factors contributed by two divergent diploids become united in a common nucleus. Although these regulatory patterns have been explored in various plant systems (Springer & Stupar, ; Chaudhary et al ., ; Shi et al ., ; Bell et al ., ; Lemmon et al ., ; Xu et al ., ; Combes et al ., ; He et al ., ), we point out here that the classic ASE model fails to adequately parse the various forms of cis–trans interactions that are created by allopolyploidy. As such, advancing our understanding of the molecular and regulatory basis of phenotypic innovations that emerge following allopolyploidization requires this model to be extended.…”
mentioning
confidence: 99%